The World Bank Group A to Z - World Bank Group (Washington, DC, 2014)
Note: Information in this title reflected the institution at the time of publication and may be subject to change... The World Bank Group (also known as the “Bank Group”) is the largest anti-poverty institution in the world, offering loans, advice, knowledge, and an array of customized resources to more than 100 developing countries and countries in transition. Established in 1944 and headquartered in Washington DC, the Bank Group is a specialized agency of the United Nations that is made up of 188 member countries. It works with country governments, the private sector, civil society organizations (CSOs), regional development banks, think tanks, and other international institutions on a range of issues—from climate change, conflict, and food crises to education, agriculture, finance, and trade—with the sole purpose of meeting two goals: ending extreme poverty by 2030 and boosting shared prosperity of the bottom 40 percent of the population in all developing countries.